Revolutionizing Waste Systems with AI Intelligence, IoT Connectivity, and Blockchain Integrity - Vishal Bhagat; Tanisha Gupta; Saurabh Gupta; Dr. Nikhat Akhtar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Population expansion and evolving consumption trends make trash management a critical worldwide issue. Research indicates that by 2050, about 67% of the global population will reside in megacities, necessitating intelligent solutions to address inhabitants’ needs. Waste collection is an effective IoT service that leverages cost and energy efficiency. This research investigates the revolutionary capabilities of Artificial Intelligence (AI) and the Internet of Things (IoT) in enhancing garbage management via intelligent collection, automated sorting, real-time monitoring, and predictive analytics. Artificial intelligence-based garbage categorization enhances recycling effectiveness, whilst Internet of Things-enabled smart bins streamline collection routes, hence decreasing operating expenses and reliance on landfills. Blockchain, a technology facilitating decentralized and immutable ledgers, is being re-envisioned as a means to transform waste management. This novel methodology seeks to enhance trash management transparency, traceability, and efficiency, yielding substantial environmental and economic advantages. Conventional waste management systems lack transparency in the monitoring and disposal of waste products, rendering them susceptible to fraud, mismanagement, and inefficiency. Blockchain technology offers a safe and transparent framework for documenting each phase of the waste management lifecycle, including trash creation, collection, transportation, recycling, and disposal. Each transaction in the blockchain is documented in an immutable fashion, facilitating real-time oversight and validation of waste-related information. This article presents the use of blockchain technology in garbage management. The primary objective of this study is to demonstrate the use of blockchain technology into an established waste management firm, using smart contracts in the recycling process to enhance transparency. The digital product passport was redefined for the circular economy and trash recycling.